Analisis tentang Iklim Organisasi - Harlie, M. (Jurnal Aplikasi Manajemen, 2008)
Organization culture essentially reflects culture, tradition and attitude pattern followed by certain organization. Any significant variables affecting organization climate needs to be collectively understood in an organization. Any attempts to evaluate good or not certain organization need executing. Healthy organization climate will give effect on such organization improvement. Therefore such condition need to be continously created.